The applying of the hyper-text means for the electronic technical products designing documents pre-working - Grigoriev, Vitaliy; Tolochko, Irina (Видавництво Національного університету "Львівська політехніка", 2002)
The electronic products designing documents hyper-text system structure, building principles, software and informational supplying are considered. By the specification record activising the system allows to find and load the appropriative software for the visualising and editing the designing document or product included by the electronic device.
Keywords: hyper-text system; designing documents